ANALYSIS OF THE RELATIONSHIP OF E-COMMERCE TRANSACTIONS, INTERNET USERS, FOREIGN CAPI-TAL AND LABOR TO INDONESIAN ECONOMIC GROWTH - Rosadi, Fachrial Djannah; Hutasoit, Anita N; Fauji, Irfan; PANE, SANUSI GAZALI (Inovbiz: Jurnal Inovasi Bisnis, 2024)
Economic growth is influenced by E-commerce and several variables, the other variables are Labor, Internet Users and Foreign Investment. The variables used in this study are more than one variable, so the analysis method used is Vector Autoregressive (VAR). This method is used in order to see the relationship between variables which is one of the multivariate analyzes for time series data. This research uses data on E-commerce Transactions, Labor, GDP, Internet Users and Foreign Investment for the period January 2019-December 2022. The results of the forecast in this study using the VAR method can be seen that the variables with the first largest contribution to GDP is GDP itself and the Labor. As for the first largest contribution to E-commerce Transactions are the variables themselves, Economic Growth, and Foreign Investment